An assessment of Malaysia’s fiscal deficit and current account balance using a nonlinear approach - Ramasamy, Kanageswary; Said, Rusmawati; Ismail, Normaz Wana (Universiti Putra Malaysia, 2024)
Amidst the COVID-19 crisis, the Malaysian government responded decisively, implementing substantial fiscal expansion measures to combat the pandemic's spread and safeguard the economy. In the second quarter of 2020, the current account surplus decreased to RM5.6 billion, or 1.7% of GDP, raising concerns of a twin-deficit. Keynesians relate fiscal deficits to the twin-deficit hypothesis. This study will use data from 2008Q1 to 2022Q4 to investigate the validity of the theory on Malaysia in the aftermath of the COVID-19 pandemic. For empirical analysis, the Nonlinear Autoregressive Distributed Lag (NARDL) approach will be used. Results show that fiscal deficits have neither short- or long-run effect on the current account, confirming the Ricardian Equivalence Hypothesis (REH), which holds that fiscal deficits do not affect the current account balance. In addition, research findings confirm the significance of economic growth and exchange rates in augmenting the surplus of the current account. Therefore, it is crucial to prioritise the successful execution of the National Investment Master Plan 2030, the Twelfth Malaysia Plan, and the New Industrial Master Plan 2030 in order to effectively address the prevailing economic challenges. These efforts have the potential to boost economic revitalization and foster long-term growth.